Assessment of biochemical alterations in the neotropical fish species Phalloceros harpagos after acute and chronic exposure to the drugs paracetamol and propranolol - Pereira, Beatriz V. R. (2022)
Over time, many pollutants of anthropogenic origin have caused the contamination of aquatic ecosystems. Among several characteristics, these compounds can reach the trophic chain, causing deleterious interactions with the biota. Pharmaceutical substances can be included in this scenario as emerging contaminants that reach the aquatic environment because of direct human and veterinary usage, and release by industrial effluents, as well as through domestic dumping of surplus drugs. The effects of these compounds on exposed organisms have been studied since the 1990s, but ecotoxicological data for such chemicals are still scarce especially concerning aquatic organisms from tropical regions. Paracetamol and propranolol were selected for this study since they are frequently found in surface waters. Paracetamol is a drug used as analgesic and antipyretic, while propranolol, a β-blocker, is used in the treatment of hypertension. The objective of this study was to assess the toxic effects of these substances on the neotropical freshwater fish Phalloceros harpagos after acute (96 h) and chronic (28 days) exposures. In order to understand the effects of these drugs on P. harpagos, biochemical markers were selected, including the enzymes involved in oxidative stress, xenobiotic metabolism, and neurotransmission (catalase, glutathione-S-transferase, and cholinesterase activities, respectively). After acute exposure, no significant alterations were observed for catalase activity, suggesting the absence of oxidative stress. On the contrary, significant alterations in glutathione-S-transferases activity were described for the higher concentrations of both pharmaceuticals after acute exposure. In addition, acute exposure to paracetamol caused a significant increase of cholinesterase activity. None of the tested pharmaceuticals caused significant changes in catalase or cholinesterase activities after chronic exposure. Glutathione S-transferases activity was significantly increased for propranolol following chronic exposure, indicating the potential involvement of phase II detoxification pathway.